VD_FINDINFO Jug / 2023 / 348 vom 21. Februar 2023 - VD Tribunal cantonal (2023)
ESCROQUERIE, PERCEPTION ABUSIVE DE PRESTATIONS DE L'AIDE SOCIALE, SURSIS À L'EXÉCUTION DE LA PEINE, AMENDE | 106 CP, 146 al. 1 CP, 34 CP, 42 al. 1 CP, 42 al. 4 CP, 44 al. 1 CP, 47 CP